Anti-hyperlipidemic caffeoylquinic acids from the fruits of Pandanus tectorius Soland - Huiling Liu, Xiaopo Zhang & , Chongming Wu, Haifeng Wu, Peng Guo, Xudong Xu (Journal of Applied Pharmaceutical Science, 2013)
Ten caffeoylquinic acids (CQAs) were obtained from the anti-hyperlipidemic extract of fruits of Pandanus tectorius. All of the compounds were isolated and purified by various column chromatographies especially by preparative HPLC method. Their structures were determined under the aid of spectroscopic methods. All compounds were isolated from genus pandanus for the first time. The anti-hyperlipidemic activities of three compounds characterized with high content in the fruits were tested in HepG2 cells.The three CQAs all significantly reduced the intracellular content of TC and TG.
Keywords: Pandanus tectorius Soland, Caffeo